2017
DOI: 10.23960/jbekh.v4i1.122
|View full text |Cite
|
Sign up to set email alerts
|

Kadar Lipid Tiga Jenis Mikroalga Pada Salinitas Yang Berbeda

Abstract: Penelitian ini bertujuan untuk mengetahui laju pertumbuhan dan kandungan lipid pada ketiga jenis mikroalga yang dikultur pada media dengan salinitas yang berbeda. Penelitian dilakukan dengan menggunakan metode rancangan acak lengkap faktorial dengan 3 perlakuan yaitu salinitas 20, 30, dan 40 ppt pada mikroalga jenis Nannochloropsis sp., Tetraselmis sp., dan Porpyridium sp masing-masing sebanyak 3 kali ulangan. Mikroalga dikultur pada skala laboratorium selama 8 hari setelah itu dipanen untuk diukur kadar lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…Other study indicated that microalgae Tetraselmis sp. had the highest percentage of increasing in population at salinity of 20 ppt with cell density of 677.78 x 10 4 cells/mL [16] . Most of the microalgae tolerated the conditions of environmental changes such as salinity with a very large range and most species of microalgae well performed growth in salinity which was slightly lower than the condition of salinity in its natural habitat [17].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Other study indicated that microalgae Tetraselmis sp. had the highest percentage of increasing in population at salinity of 20 ppt with cell density of 677.78 x 10 4 cells/mL [16] . Most of the microalgae tolerated the conditions of environmental changes such as salinity with a very large range and most species of microalgae well performed growth in salinity which was slightly lower than the condition of salinity in its natural habitat [17].…”
Section: Resultsmentioning
confidence: 97%
“…resistant to high salinity. Study conducted by Ningsih et al [16], indicated that Tetraselmis sp. when given salinity of 30 ppt (normal) lipid level of 1.26% was produced, but when salinity had been reduced to 20 ppt the lipid content was greater than normal salinity reached to 2.64%, and when salinity was increased to 40 ppt the lipid content produced was lower up to 0.19%.…”
Section: Total Lipid Levels Of Microalgae Nitzschia Spmentioning
confidence: 99%
“…Naik turunnya salinitas mempengaruhi Thalassiosira sp. yang secara langsung mempengaruhi proses metabolisme, menyebabkan pertumbuhan populasi melambat (Ningsih et al, 2017).…”
Section: Perlakuanunclassified
“…Salinitas adalah salah satu sifat kimiawi perairan yang secara langsung maupun tidak dapat berpengaruh terhadap pertumbuhan dan aktivitas kehidupan organisme perairan (Ningsih et al, 2017). Kemampuan beradaptasi mikroalga bergantung pada jenis habitat aslinya dan perubahan salinitas.…”
Section: Perlakuanunclassified
See 1 more Smart Citation